Insights into the structure and architecture of the CCR4–NOT complex - Xu, Kun; Bai, Yuwei; Zhang, Aili; Zhang, Qionglin; Bartlam, Mark G. (Frontiers in Genetics, 2014)
The CCR4–NOT complex is a highly conserved, multifunctional machinery with a general role in controlling mRNA metabolism. It has been implicated in a number of different aspects of mRNA and protein expression, including mRNA degradation, transcription initiation and elongation, ubiquitination, and protein modification. The core CCR4–NOT complex is evolutionarily conserved and consists of at least three NOT proteins and two catalytic subunits. The L-shaped complex is characterized by two functional modules bound to the CNOT1/Not1 scaffold protein: the deadenylase or nuclease module containing two enzymes required for deadenylation, and the NOT module. In this review, we will summarize the currently available information regarding the three-dimensional structure and assembly of the CCR4–NOT complex, in order to provide insight into its roles in mRNA degradation and other biological processes.